Political and Educational Messages in Serambi Indonesia: A Framing Analysis - Saiful Akmal; Abdul Rani Usman; Qamaruzzaman Qamaruzzaman (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
The existence of the media in social life is essential. Apart from providing a forum for distributing information, the media also play an important role to control the government performance. However, the media often frames reality and at the same time, published news from multiple angles; as this can affect the process of defining the truth constructed in their framing. This study analyzes the news framing published the Kuta Raja rubric, Serambi Indonesia daily in Aceh, especially those contain political and educational message. This present study employed a qualitative descriptive approach with the data collected from July to September 2020. The data were analyzed thematically and analytically in descriptive stages. The results indicate that the Kuta Raja rubric is often f shown by highlighting certain aspects of the news, such as displaying dominant political figures. In contrast, the educational information is not very significantly emphasized. Thus, it is necessary to have a balance in the reconstruction process of an event in order to avoid framing bias.